Context, culture and (non-verbal) communication affect handover quality. Issue 1 (21st November 2012) - Frankel, Richard M; Flanagan, Mindy; Ebright, Patricia; Bergman, Alicia; O'Brien, Colleen M; Franks, Zamal; Allen, Andrew; Harris, Angela; Saleem, Jason J
Abstract : Background: Transfers of care, also known as handovers, remain a substantial patient safety risk. Although research on handovers has been done since the 1980s, the science is incomplete. Surprisingly few interventions have been rigorously evaluated and, of those that have, few have resulted in long-term positive change. Researchers, both in medicine and other high reliability industries, agree that face-to-face handovers are the most reliable. It is not clear, however, what the term face-to-face means in actual practice. Objectives: We studied the use of non-verbal behaviours, including gesture, posture, bodily orientation, facial expression, eye contact and physical distance, in the delivery of information during face-to-face handovers. Methods: To address this question and study the role of non-verbal behaviour on the quality and accuracy of handovers, we videotaped 52 nursing, medicine and surgery handovers covering 238 patients. Videotapes were analysed using immersion/crystallisation methods of qualitative data analysis. A team of six researchers met weekly for 18 months to view videos together using a consensus-building approach. Consensus was achieved on verbal, non-verbal, and physical themes and patterns observed in the data. Results: We observed four patterns of non-verbal behaviour (NVB) during handovers: (1) joint focus of attention; (2) 'the poker hand'; (3) parallel play and (4) kerbside consultation. In terms of safety, joint focus of attention was deemed to have the best potential for high quality and reliability; however, it occurred infrequently, creating opportunities for education and improvement. Conclusions: Attention to patterns of NVB in face-to-face handovers coupled with education and practice can improve quality and reliability.